PENGARUH KINERJA LINGKUNGAN DAN KEPEMILIKAN INSTITUSIONAL MELALUI KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2024) - Nur Arifani, Haula; Christiani, Veronica (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this study is to determine the effect of environmental performance and institutional ownership through financial performance on firm value in energy sector companies listed on the Indonesia Stock Exchange. This study uses secondary data in the form of annual financial reports of energy companies listed on the IDX for the period 2019 to 2024 and environmental performance rating (PROPER) data taken from the Ministry of Forestry and Environment. The sample taken was 18 energy sector companies and the analytical technique used in this study was multiple linear regression analysis